Legal regulation of GMO introduction: problems and ways of their solution.ГТА айналымын құқықтық реттеу: проблемалар және шешу жолдары. - G. T. Aigarinova. (Хабаршы. Заң сериясы, 2016)
This article is devoted to the problems of legal regulation of GMOs introduction. The study lies in comprehensive research of modern ecological and legal problems on the basis of analyzing international, foreign and national legislation in the field of legal regulation of GMOs and use of chemicals in agricultural production. In this regard, proposals to improve and fill gaps in the current legislation of the Republic of Kazakhstan are worked out. Нақты мақала гендік түрлендіріліген ағзалардың айналымын құқықтық реттеу мәселелеріне арналған. Зерттеу ГТА айналымы және ауылшаруашылығында химиялық заттарды пайдалануды құқықтық реттеу саласында халықаралық, шетелдік және ұлттық заңнамалардың негізінде заманауи экологиялық проблемаларды зерттеуге бағытталған.